How do males recover from eating disorders? An interview study - Pettersen, Gunn (BMJ Open, 2016)
OBJECTIVES: The aim of the current study is to investigate what males experience as helpful in their recovery process from eating disorders (ED). METHODS: Qualitative in-depth interviews within a phenomenological approach, and using content analysis to excavate overarching text themes. SETTING: Norway and Sweden. PARTICIPANTS: Included were 15 males with an age range from 19 to 52 years. Duration of illness varied between 3 and 25 years of experience with anorexia nervosa (n=10), bulimia nervosa (n=4) or ED not otherwise specified (n=1). RESULTS: The content analysis revealed four main categories, that is, ‘the need for a change’, ‘a commitment to leave the eating disorder behind’, ‘interpersonal changes’ and ‘searching for a life without an eating disorder’. These categories comprise features like motivation to change, gaining structure in eating situations, a re-learning of personal and interpersonal skills as well as accepting losses and starting a reorientation of identity and meaning. We noted a rather goal-oriented approach to help seeking and a variation in how the males engaged their social network in resolving the challenges associated with the recovery process. Still, the overall nature of the recovery process highly accords with what has been reported for women. DISCUSSION: A clinical implication from our findings is that symptom relief is important to facilitate good circles of improvement, but that the nature of the recovery process would require a wider perspective in treatment. Clinicians may also be informed about challenges related to an instrumental approach to help seeking reported in this study.